If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7 + 6x + 15 = 90 Reorder the terms: 7 + 15 + 7x + 6x = 90 Combine like terms: 7 + 15 = 22 22 + 7x + 6x = 90 Combine like terms: 7x + 6x = 13x 22 + 13x = 90 Solving 22 + 13x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 13x = 90 + -22 Combine like terms: 22 + -22 = 0 0 + 13x = 90 + -22 13x = 90 + -22 Combine like terms: 90 + -22 = 68 13x = 68 Divide each side by '13'. x = 5.230769231 Simplifying x = 5.230769231
| 2w+8=0 | | x^2+y^2-8x-10y-8=0 | | (3x-2)(9x+5)=0 | | 25x^2-15x-6=0 | | 1.2w+5=7.4 | | 5y+13=0 | | -6y-28=0 | | 3(2x+1)=2(3+2x)-3 | | Y=(c-b)x+6 | | -2v+9=0 | | 3(2x-5)-(4x+1)=5(x+3)-2 | | 6.3=.09y | | sin(x-3)=cos(2x+6) | | 8h-28=36 | | 6z+10=2080 | | 3s+9t+4t= | | (-31)-(43)= | | 3(x-2)-(2-5x)=4-6(2-3)-7x | | 9x-6=2x+36 | | 12b-8=4 | | 25x^2+15X-6=0 | | (-18)-(-39)= | | 8a-a=16 | | 5x-48=1x | | 4v-16=-9 | | (-27)-(-50)= | | x+x+3x=3 | | 1+6(2+3)= | | 0=-6w+30 | | (-9)-(9)= | | y+14=4 | | (25)-(8)= |